2010
DOI: 10.1158/0008-5472.can-10-1852
|View full text |Cite
|
Sign up to set email alerts
|

Active Immunotherapy Induces Antibody Responses That Target Tumor Angiogenesis

Abstract: The inhibition of VEGF signaling with antibodies or small molecules achieves clinical benefits in diverse solid malignancies. Nonetheless, therapeutic effects are usually not sustained, and most patients eventually succumb to progressive disease, indicating that antiangiogenic strategies require additional optimization. Vaccination with lethally irradiated, autologous tumor cells engineered to secrete granulocyte-macrophage colony stimulating factor (GM-CSF) and antibody blockade of cytotoxic T lymphocyte-asso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 37 publications
(43 reference statements)
0
88
0
Order By: Relevance
“…34 Antibody responses developed towards neovessels following immunization were instrumental to create ischemic tumor necrosis. 35 Hence, GM-CSF-engineered tumor vaccines combined with anti-CTLA4 engendered a co-ordinated cellular and humoral immunity associated with clinically significant tumor regressions in advanced solid cancers. 36 In such regressing tumor burdens, T cell infiltrates were juxtaposed to antibody-producing B cells in long-term responders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Antibody responses developed towards neovessels following immunization were instrumental to create ischemic tumor necrosis. 35 Hence, GM-CSF-engineered tumor vaccines combined with anti-CTLA4 engendered a co-ordinated cellular and humoral immunity associated with clinically significant tumor regressions in advanced solid cancers. 36 In such regressing tumor burdens, T cell infiltrates were juxtaposed to antibody-producing B cells in long-term responders.…”
Section: Discussionmentioning
confidence: 99%
“…Humoral reactivity was reported against proangiogenic cytokines such as angiopoietin-1 and -2 blocking the endothelial cell tube formation and/or macrophage inhibitory factor attenuating macrophage Tie-2 and MMP9 expression. 35 Likewise, antibodies against protein disulfide isomerases (PDI, ERp5, 37 ) or an accessory unit of the vacuolar H þ -ATPase complex 38 appeared of clinical significance. These data are in line with other observations, stating that the presence of tertiary lymphoid organogenesis (TLO), high endothelial venules (HEV) or germinal centers (GC) residing around the tumor nests are associated with good prognosis in breast carcinoma, non-small cell lung cancer and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacologic inhibition of the SDF1/CXCR4 axis prevented their influx to irradiated tumors and inhibited postirradiation development of a functional tumor vasculature, resulting in abrogation of tumor relapse (33). A recent report showed that vaccination with irradiated, autologous tumor cells engineered to secrete granulocytemacrophage colony stimulating factor and antibody blockade of cytotoxic T lymphocyte-associated antigen-4 triggered a tumor vasculopathy in some long-term responding patients with solid cancer (53). These reactions were associated with important humoral reactions against multiple angiogenic cytokines, including ANG2.…”
Section: Ang2 Blockade: Clinical Developmentmentioning
confidence: 99%
“…A survival benefit for ADC patients treated with a monoclonal antibody against vascular endothelial growth factor A (VEGF-A), bevacizumab, combined with standard platinum based chemotherapy (carboplatin plus paclitaxel) was demonstrated, although accompanied by greatly increased toxicity (Sandler et al, 2006). However, combination of immunotherapies with anti-angiogenic agents has been reported to be effective and potentially beneficial for the clinical outcome of NSCLC patients (Schoenfeld et al, 2010) Potential combination therapy including agents targeting different tumor features, such as additional oncogenic aberrations, signaling from stromal cells, metabolic alterations and angiogenesis, as well as immunotherapy approaches to treat lung ADC (Fig. 2) are underway.…”
Section: Combinatory Treatment Of Lung Adenocarcinomamentioning
confidence: 99%